THE IMPROVEMENT OF THE UNDERSTANDING OF SERVICE AND FIGURE ROLE OF INDONESIAN INDEPENDENCE CONCEPT THROUGH TEAMS GAMES TOURNAMENT MODEL HELPED BY ROTAR MEDIA - Dede Eka Putri; Endang Sri Markamah; Sadiman Sadiman (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This research aims to improve understanding of service and figure role Indonesian independence concept at 5th grade student of elementary school in Surakarta by application of Teams Games Tournament (TGT) model helped by rotar media.This research was classroom action resarch which was held i two cycles, there were four stage in each cycle, which planning, implementation, observation, and reflection. The subjects were a teacher and 34 students. The data sources are form the teacher and student. The technics of collecting data are test, interview, observation, and documentary. Data analysis were interactive analysis. According to the research conclusion, Teams Games Tournament model helped by rotar media could improve understanding of service and figure role of independence concept at 5th grade student of elementary school in Surakarta academic year 2017/2018. That improvement could be Pre-action, the percentage of class attainment is only 5,88% then at second cycle, the percentage of class attainment increases to 88,24%